Strengthening the Surveillance of Antimicrobial Resistance in India Using Integrative Technologies - Kaur, Jasleen; Kaur, Jasmine; Dhama, Ajay Singh; Jindal, Shelja; Walia, Kamini; Singh, Harpreet (Frontiers in Public Health, 2022)
Background: The AMR situation in India is alarming. India is among the countries with the highest antibiotic consumption as well as resistance rates. A one-stop data repository for the country is imperative to drive data-driven decision-making. Thus, it is essential to have tools that can capture data from varied sources into a single database. Methods: An ensemble of tools (i-AMRSS, i-DIA, and i-AMRIT) have been designed & developed by the data management team at the Indian Council of Medical Research (ICMR) for strengthening the surveillance of antimicrobial resistance in India. Results: The i-AMRSS is a web-based ICMR’s AMR surveillance system, collecting data from tertiary care centers across the country and sending it to the one-stop repository. The i-DIA is a web-based API that simplifies the AMR data interoperability by seamlessly importing the majority of LIS / HIS data from CSV files into a central one-stop data repository. The i-AMRIT is a standalone ICMR’s AMR surveillance system using integrative technologies, collecting data from all the labs across the country and sending the lab-specific cumulative data to the one-stop repository. Discussion: The tools are piloted in ICMR’s AMR Network (more than 25tertiary-care hospitals across India). To date, the one-stop repository has collected over 4 lakh patient records. The complete system is presently being used for capturing human susceptibility testing data, however, it can be extended for AMR surveillance using the ‘One Health’ approach. The authors plan to make the system compliant with FHIR standards to enable interoperability with other countries as well.